The Influence Of Profitability, Asset Structure And Company Size On The Performance Of Manufacturing Company Shares That Go Public On The Indonesia Stock Exchange - Jumriah Basri; A. Kartini Sari Putri D (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
The results showed that based on the results of the regression test that partially Profitability has a positive and insignificant effect on stock performance in manufacturing companies listed on the Indonesia Stock Exchange, asset structure has a negative and insignificant effect on stock performance in manufacturing companies listed on the Indonesian Stock Exchange, Company size has a positive and significant effect on stock performance in manufacturing companies listed on the Indonesia Stock Exchange, while simultaneously profitability, asset structure and company size have a significant and significant effect on stock performance in manufacturing companies listed on the Indonesia Stock Exchange.